PERGESERAN PARADIGMA TAFSIR ALA LINGUIS: (Memamahi Ide Pembaruan dan Model Penafsiran M. Syahrur) - John Supriyanto (STIQ al-Lathifiyyah Palembang, 2018)
This paper tries to explore one of the children's understanding of the knowledge of the Qur'an and tafsir. Muhammad Syahrur ad-Dayyub, a linguist and based on civil engineering, offers a new approach to understanding the Qur'an. Syahrur's ideas about the Qur'an which he published in